2018
DOI: 10.4102/safp.v60i2.4827
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic Options for Ophthalmic Conjunctivitis

Abstract: Conjunctivitis is a common eye condition involving inflammation and in some instances infection of the conjunctiva. In the majority of cases it is caused by adenoviruses and to a lesser extent bacteria. Conjunctivitis can also occur secondary to Chlamydial and Gonococcal infections and new-born infants can acquire it during the birthing process from infected mothers. Herpes simplex and Herpes zoster are the infective organisms also responsible for conjunctivitis while seasonal pollens are usually the cause for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Fucidic acid is not a first-line agent due to the increased risk of resistance. 4 Generally, fucidic acid is considered to have a narrow spectrum of activity which predominantly covers staphylococcal infections such as blepharitis or conjunctivitis. However, in a Canadian study that compared the topical use of 1% fusidic acid to 0.3% tobramycin to treat acute bacterial conjunctivitis, no difference in efficacy was demonstrated between the two drugs.…”
Section: Fucidic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucidic acid is not a first-line agent due to the increased risk of resistance. 4 Generally, fucidic acid is considered to have a narrow spectrum of activity which predominantly covers staphylococcal infections such as blepharitis or conjunctivitis. However, in a Canadian study that compared the topical use of 1% fusidic acid to 0.3% tobramycin to treat acute bacterial conjunctivitis, no difference in efficacy was demonstrated between the two drugs.…”
Section: Fucidic Acidmentioning
confidence: 99%
“…To limit adverse effects and resistance from developing, chloramphenicol should not be used for longer than five days. 4 The ocular toxicity of topical chloramphenicol is low, although it may serve as a trigger for delayed allergic contact dermatitis or conjunctivitis. Aplastic anaemia and other blood dyscrasias have been linked to the ocular use of chloramphenicol, although it has been shown that the risk is less than one per million treatment courses.…”
Section: Chloramphenicolmentioning
confidence: 99%
“…There are a number of drugs that can be used to treat conjunctivitis depending upon the cause, that is, antibacterial agents (bacterial conjunctivitis), antiviral agents (viral conjunctivitis), antihistamines, glucocorticosteroids (allergic conjunctivitis), and so forth. [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Conjunctivitis, an inflammatory eye infection, involves the conjunctiva. Due to blood vessel dilation, which causes hyperemia and conjunctival edema, it appears as the red or pink eye [1]. There are a number of drugs that can be used to treat conjunctivitis depending upon the cause, that is, antibacterial agents (bacterial conjunctivitis), antiviral agents (viral conjunctivitis), antihistamines, glucocorticosteroids (allergic conjunctivitis), and so forth.…”
Section: Introductionmentioning
confidence: 99%